POLA PEMBERDAYAAN MASYARAKAT DI HULU SUB DAERAH ALIRAN SUNGAI MIU (KASUS PENERAPAN PROGRAM SCBFWM DI DESA BOLADANGKO KECEMATAN KULAWI KABUAPTEN SIGI PROVINSI SULAWESI TENGAH) - Idhar, Moh.; Golar, Golar; Sudhartono, Arif (Jurnal Warta Rimba, 2015)
Sub watershed catchment of Miu river sited in Sigi Regency has 70.494,5 hectoare width which part of it in critical land status. The community use the land just for economic reason for fulfill their daily needed without think about how to manage the land in order to get its continuous productivity and along time periode of land using. SCBFWM project is an empowering community program around of sub watershed catchment of Miu river that it is ordered to decrease forest and land degradation level and to recovery watershed catchment function. The aim of this research was pointed to know any kind of the empowering community program, accompanying methode, and their constraints of SCBFWM project implementation. This research is conducted in upperside of sub watershed catchment of Miu river, Boladangko village, Kulawi district, Sigi regency, Central Celebes province as along as two months (February up to April 2014) used survay and interview methodes; interview guidance forwarded to 25 respondences (that consisted are field facilitator, common society, and farmer group members); additional informations and data confirmation from respondences used snowball sampling methode. The supporting tools of this research are tape recorder, camera, and writing tools. This research results have shown that the empowering community pattern of SCBFWM project include forming of farmer groups, training in be autonomous institution of farmer group, continuous socialization, land rehabilitation, diversing agriculture and husbandry business, upgrading of institution structure and accompanion of farmer group. Accompanying methode on SCBFWM project implementation are strengthening on changing of thinking pattern and changing activities based on increasing economic farmer. The main constraints of SCBFWM project implementation are less level on funding support from related stakeholders on implementation of empowering community program and lowness of farmer group member participation on mounthly meeting. Keywords: empowering pattern, Miu river, SCBFWM, watershed catchment.